Suprasellar Meningioma Classification: Endoscopic Transnasal Perspective - Ajlan, Abdulrazag; Noor Elahi, Basim; Almeshari, Saif; Basindwah, Sarah; Alghabban, Fatimah Abdulrahim; Alromaih, Saud; Alroqi, Ahmad; Alrasheed, Abdulaziz S.; Alqurashi, Ashwag; Alsaleh, Saad (Journal of Neurological Surgery Part B: Skull Base, 2023)
Objectives Midline suprasellar meningiomas include planum sphenoidale, tuberculum sellae, and diaphragma sellae meningiomas. Multiple classifications have been previously documented; however, they come with controversies and limitations, including those with surgical implications. The aim of this study was to classify suprasellar meningiomas based on their behavior toward the underlying bone and neurovascular structures.Methods Patients with newly diagnosed suprasellar meningiomas that underwent extended endoscopic transnasal approach between 2015 and 2021 were included in this study. The following parameters were evaluated: chiasmatic sulcus length, location of the optic chiasm and nerves, optic canal involvement, and vascular displacement.Results We identified 40 cases of midline suprasellar meningiomas, 1 diaphragma sellae meningioma (type A), 10 tuberculum sellae meningiomas (type B), 9 chiasmatic sulcus meningiomas (type C), and 10 planum sphenoidale meningiomas (type D). Asymmetrical visual complaints were most common in chiasmatic sulcus meningiomas, followed by tuberculum sellae meningiomas (66 and 50%, respectively). Chiasmatic sulcus meningiomas showed increased separation between the optic chiasm and the A1/A2 complex (8.9 mm) compared with tuberculum sellae (2.7 mm) and planum sphenoidale (1.9 mm) meningiomas. Compared with other types, increased chiasmatic sulcus length was observed in chiasmatic sulcus meningiomas.Conclusion Preoperative evaluation of bone involvement and tumor relation to neurovascular structures can be used to classify suprasellar meningiomas. Chiasmatic sulcus meningioma is a distinct subtype of suprasellar meningiomas. Its unique behavior toward nearby neurovascular structures could be of surgical value during tumor resection.
Keywords: meningioma; suprasellar; chiasmatic sulcus